A Measure of Intense in West and Central Java Through Manifestation of River Basin Morphometry Development on Quaternary Volcanic Deposits - Febri Hirnawan (Geological Agency, 2009)
DOI: 10.17014/ijog.v4i4.88Indications exhibiting active tectonic movements in Java occur in many places, characterized by unstable regions, such as active faults, earthquakes, volcanic eruptions, etc. The results of researches conducted at several areas in West and Central Java on tectonic morphometry developments of river basins both in Quaternary deposits and Tertiary sediments exhibit a degree of active tectonic intensity. Such the researches are very important regarding to the spatial development design that is related to a region of active tectonism that should be well understood by planners for decision making mainly through comprehensive approach, in which the phenomena involved explaining the characteristics of the region as part of an active plate margin. Statistic approach as the chosen methodology had been utilized to gain meaningful conclusions through the verification of hypotheses, which are based on valid and reliable tested data obtained from the fields and satellite imagery. Results of regression-correlation tests between azimuths of river segment and lineaments in both chronostratigraphic systems mentioned earlier are significant with several large values of correlation coefficients r of no less than 0.9. On the other hand, results of t-tests are not a significant difference of means of bifurcation ratio (Rb) and drainage density (Dd) from many to river basins. The results of all tests have verified the effect of active tectonic control on the morphometry development process regarding to river segments and density of drainage patterns development in Tertiary and Quaternary deposits.